Hydrolysate from mussel mytilus galloprovincialis meat: enzymatic hydrolysis, optimization and bioactive properties - Cunha, Sara A. (2021)
Mussel production generates losses and waste since their commercialisation must be aligned with target market criteria. Since mussels are rich in proteins, their meat can be explored as a source of bioactive hydrolysates. Thus, the main objective of this study was to establish the optimal production conditions through two Box–Behnken designs to produce, by enzymatic hydrolysis (using subtilisin and corolase), hydrolysates rich in proteins and with bioactive properties. The factorial design allowed for the evaluation of the effects of three factors (hydrolysis temperature, enzyme ratio, and hydrolysis time) on protein/peptides release as well as antioxidant and anti-hypertensive properties of the hydrolysates. The hydrolysates produced using the optimised conditions using the subtilisin protease showed 45.0 ± 0.38% of protein, antioxidant activity via ORAC method of 485.63 ± 60.65 µmol TE/g of hydrolysate, and an IC50 for the inhibition of ACE of 1.0 ± 0.56 mg of protein/mL. The hydrolysates produced using corolase showed 46.35 ± 1.12% of protein, antioxidant activity of 389.48 ± 0.21 µmol TE/g of hydrolysate, and an IC50 for the inhibition of ACE of 3.7 ± 0.33 mg of protein/mL. Mussel meat losses and waste can be used as a source of hydrolysates rich in peptides with relevant bioactive properties, and showing potential for use as ingredients in different industries, such as food and cosmetics, contributing to a circular economy and reducing world waste.